Efecto del visual merchandising en la decisión de compra de prendas de vestir en la tienda por departamento Saga Falabella - Martins Fernández, Ana Lucia (2023)
Through this research, it is intended to have a knowledge of the effect of visual merchandising in the decision to buy clothing in the Saga Falabella department stores in Metropolitan Lima. In this study, the elements of visual merchandising are categorized into two sections, organization of the exterior of the business and organization of the interior of the business. The exterior elements are label, showcase and entrance. The elements of the interior of the business are signs, lighting, decoration, aroma and music. Therefore, the main objectives to be analyzed focused on determining the elements of visual merchandising that have a greater influence on the purchase decision and the generation that is most influenced by visual merchandising when making a garment purchase decision. to dress at the point of sale. The research was quantitative, correlational and with a non-experimental design in order to have knowledge of the relationship that exists between both study variables. Therefore, a survey was applied to 384 people through a questionnaire with 21 questions. From the data collected, it was identified that the visual merchandising elements with the greatest impact on the purchase decision of consumers in the Saga Falabella department stores are shop windows, mannequins and lighting. Equally significant are the signs for offers and brands of apparel and interior décor because when consumers are exposed to visual stimuli, they are more likely to make unplanned purchasing decisions.